2021
DOI: 10.1192/bjo.2020.169
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse outcome of COVID-19 among patients in secure psychiatric services: observational cohort study

Abstract: Background Secure forensic mental health services treat patients with high rates of treatment-resistant psychoses. High rates of obesity and medical comorbidities are common. Population-based studies have identified high-risk groups in the event of SARS-CoV-2 infection, including those with problems such as obesity, lung disease and immune-compromising conditions. Structured assessment tools exist to ascertain the risk of adverse outcome in the event of SARS-CoV-2 infection. Aims To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Forensic psychiatric patients have been met with similar challenges ( Kennedy et al, 2020 ). In a recent study, almost a third of forensic patients were found to be at high risk for adverse outcomes if infected with COVID-19 ( Basrak et al, 2021 ). Moreover, when restricted to hospital units, physical distancing becomes difficult, and patients are deprived of previous liberties, access to the community, and communication with friends and family ( Simpson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Forensic psychiatric patients have been met with similar challenges ( Kennedy et al, 2020 ). In a recent study, almost a third of forensic patients were found to be at high risk for adverse outcomes if infected with COVID-19 ( Basrak et al, 2021 ). Moreover, when restricted to hospital units, physical distancing becomes difficult, and patients are deprived of previous liberties, access to the community, and communication with friends and family ( Simpson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence demonstrating the association between psychiatric and substance use disorders and poor physical health across a number of domains [ 13 ▪ , 15 , 22 , 23 ▪ , 24 ], all of which increase the risk of contracting COVID-19 and experiencing more severe COVID-19-related complications if infected [ 22 , 23 ▪ , 25 27 ]. High rates of smoking, overweight and obesity, metabolic syndrome, hypertension and cardiovascular disease, alongside confinement in forensic, residential and in-patient facilities, can increase susceptibility to infection and disease [ 28 ▪▪ , 29 ]. Preexisting psychiatric symptoms may be exacerbated due to fear and worry about being infected, social isolation and the lack of connectivity, distressing medical symptoms and death [ 28 ▪▪ , 30 ▪▪ ].…”
Section: Multimorbidity Covid-19-related Complications and Pharmacotherapy Interactionsmentioning
confidence: 99%
“…Forensic mental health service users are highly vulnerable to adverse COVID-19 outcomes due to risk factors such as obesity, hypertension, metabolic syndrome, and neurocognitive impairments ( 11 ), and the nature of these services means that positive cases can spread quickly if not isolated ( 12 ). Almost one-third of service users within a forensic mental health service meet high risk age criteria, perhaps suggesting a greater than expected risk of adverse outcomes in the event COVID-19 infection ( 11 ).…”
Section: Introductionmentioning
confidence: 99%